Kajian pelaksanaan kegiatan pencegahan kebakaran hutan dan lahan di Provinsi Papua Barat - Tasurruni Tasurruni; Bambang Nugroho; Rudi A. Maturbong (Cassowary, 2019)
West Papua Province with total burned area of 8.211 Ha covering 2.792 Ha of peatland and 5.429 Ha non-peatland area. The impact of these fires are a very thick smog for a few days. The event was supported by El Nino phenomenon, in some regions, there has been a decreasing of rainfall which causes a prolonged dry season (forest and land fire). The Ministry of Environment and Forestry (KLHK) through the Center of Climate Change and Forest and Land Fire (BPPIKHL) for Maluku and Papua acting as Technical Implementation Unit (UPT) in the region, increasing the activities for forest and land fire prevention. Considering the 4 provinces work area with limited personnel, it is necessary to study the implementation of forest and land fire prevention activities. The study aims to examine the activities of forest and land fire prevention carried out by the Government, particularly BPPIKHL for Maluku and Papua in West Papua Province in relation to decreasing forest and land fires. In accordance to the studied problems, the approaching which used in this study is quantitative qualitative approach. The prioritized policy is the implementation of prevention in the site level. BPPIKHL for Maluku and Papua has carried out the activities well and effectively directly to the site level through prevention activities, which decreas the hotspots.